ANALISIS POTENSI FRAUD DALAM PEROLEHAN CASHBACK PADA APLIKASI JUAL BELI ONLINE DI APLIKASI TIKTOK - Putri, Devanny Aprillia; Miharha, Kasmanto; Azizah, Adinda Nur; Putrie, Meillanie (Universitas Trilogi, 2024)
The development of digital technology has widely impacted human lifestyles, particularly with the emergence of E-commerce and platforms like TikTok. E-commerce facilitates online buying and selling transactions, while TikTok serves as a space for content and online transactions. Cashback programs have become one of TikTok's attractive marketing strategies. However, in January 2024, there was a cashback fraud incident on TikTok that resulted in losses for consumers. This study is a qualitative field research that gathers data directly from participants, including information about TikTok's cashback policies and the cases of fraud that occurred. The findings from the field research indicate unclear inventory availability, transaction failures, and errors in the payment system. These violations are caused by TikTok employees taking on the role of consumers, hindering fairness and consumer opportunities.Keywords: Cashback; E-commerce; Fraud; TikTok